Grape root as habitat: overwintering and population dynamics of grape phylloxera (Daktulosphaira vitifoliae Fitch) in temperate climate viticulture. (18th March 2016) - Hoffmann, M.; Ruehl, E.H.; Eisenbeis, G.; Huber, L.
Abstract: Background and Aims: Daktulosphaira vitifoliae Fitch (grape phylloxera, Phylloxeridae) is one of the most devastating pests in viticulture, mainly because of their root feeding activity. Up to today fundamental relations between belowground habitat and population dynamics remain unclear. In this 2‐year study, we investigated the relations between grape phylloxera population and phenotypic traits of roots and feedings sites. Methods and Results: We extracted root and soil samples frequently of two closely related mature rootstocks [ Vitis berlandieri × V. riparia (cvs 5C and 125AA)]. We quantified and characterised larval population and crowding and assessed root gall pigmentation, root morphology and soil parameters. We identified and described three stages of seasonal population dynamics: reproduction, overwintering and declining. Further, we demonstrated a significant impact of root gall pigmentation and crowding on population dynamics. Conclusions: In temperate climates, grape phylloxera is able to overwinter at high density on roots of American rootstocks. Population dynamics are highly dependent on root gall development and the ability to crowd. Significance of the Study: The results of our study are considered to have a significant impact on the development of management strategies for grape phylloxera.